The Cross-Section of Expected Returns in the Secondary Corporate Loan Market - Beyhaghi, Mehdi; Ehsani, Sina (The Review of Asset Pricing Studies, 2017)
Corporate loans increasingly have become an important part of portfolio management with the advent of a liquid and transparent secondary market. This paper examines the pricing of characteristics and betas in the cross-section of expected loan returns. Expected loan returns decrease with default beta. Default beta contains information not captured by rating or spread-to-maturity. Among loan characteristics, a 3-month formation momentum strategy earns a monthly premium of 122 bps. Momentum is prominent in loans issued by the lowest-rated borrowers.